Responses of β‐glucosidase, permanganate oxidizable carbon, and fluorescein diacetate hydrolysis to conservation practices. Issue 5 (10th August 2021) - Xia, Yushu; Wander, Michelle
Abstract: Responsiveness of biochemical soil quality indicators (SQIs) (β‐glucosidase activity [BG], fluorescein diacetate hydrolysis [FDA], and permanganate oxidizable C [POXC]) to management and their interactions with site and experimental factors were evaluated using a meta‐database to quantify effect sizes (ESs). Eighty percent of responses were positive, with ESs ranking grassland > organic fertilizer > conservation tillage = cover crop ≥ residue return exceeding conventional controls. The ESs were, on average, larger for BG (0.34) and FDA (0.35) than POXC (0.29), and responses to site and experimental covariates varied. This work found that POXC ES was greater in soils that are drier and finer‐textured, increased with study length, varied under high and low biomass crops, and increased by use of analytical methods that recovered a larger proportion of SOC. These findings collectively suggest that POXC quantifies accumulation of protected C. Both BG and FDA were more responsive in wetter and medium‐ or coarse‐textured soils, suggesting these enzyme‐based indicators are closely associated with biologically active C. The ESs of FDA were the most spatially and temporally dynamic, exhibiting significant ( P  < .05) declines with depth and sampling time. Use of randomization tests and general linear models to quantify SQI response to management effectively identified significant covariates needed to understand differences among SQI responses to conservation management. This work demonstrated the importance of considering site and experimental covariates and a model for how to interpret SQI responsiveness using meta‐analytical summary. Core Ideas: Enzyme‐based assays were more responsive than permanganate oxidizable C to management. β‐glucosidase response was most influenced by precipitation, pH, and texture. Permanganate oxidizable C response was impacted by precipitation, SOC, pH, and crop. Fluorescein diacetate hydrolysis response varies with texture, pH, and precipitation. Analytical methods influence the responses and values of soil biochemical indicators.